2017
DOI: 10.1002/ange.201703754
|View full text |Cite
|
Sign up to set email alerts
|

A Twisted Nanographene Consisting of 96 Carbon Atoms

Abstract: Herein we report synthesis, structure and properties of a new type of twisted nanographene, which contains an [8]circulene moiety in a polycyclic framework of 96 sp2 carbon atoms. The key steps in this synthesis are the Diels–Alder reaction of a macrocyclic diyne and the subsequent Scholl reaction forming the [8]circulene moiety. Two incompletely cyclized products were isolated from the Scholl reaction, providing insight into the cyclization of the strained octagon. This nanographene is twisted along two direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…On the other hand, 6, with a slightly smaller π-system, less flexible structure and geometry more distorted from planarity, shows a rather high fluorescence quantum yield (50%), indicating more balanced radiative and nonradiative deactivation rate constants in the singlet excited state. 21,22,24,25,28,29,42,53,54 Furthermore, when the Ar-purged solutions used for the determination of the fluorescence quantum yields were left to equilibrate with air and the emission spectra were recorded, excited state quenching by molecular oxygen was detected in the case of nanographene 6 but not with 8 nor with HBC (Figure 8). In fact, a Stern− Volmer constant (K SV ) by oxygen of 215 M −1 was estimated for 6, corresponding to 34% quenching of the excited states under air-equilibrated conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…On the other hand, 6, with a slightly smaller π-system, less flexible structure and geometry more distorted from planarity, shows a rather high fluorescence quantum yield (50%), indicating more balanced radiative and nonradiative deactivation rate constants in the singlet excited state. 21,22,24,25,28,29,42,53,54 Furthermore, when the Ar-purged solutions used for the determination of the fluorescence quantum yields were left to equilibrate with air and the emission spectra were recorded, excited state quenching by molecular oxygen was detected in the case of nanographene 6 but not with 8 nor with HBC (Figure 8). In fact, a Stern− Volmer constant (K SV ) by oxygen of 215 M −1 was estimated for 6, corresponding to 34% quenching of the excited states under air-equilibrated conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The parent ene- [6]CPP 1b, ene- [8]CPP 1c, and ene- [10]CPP 1d (R = H, m = 1, 2, and 3) were synthesized by extending the synthetic method used for the synthesis of 1a starting from cis-1,2-bis(4bromophenyl)ethene (8bA, X = Br). 25 Transmetallation to the lithium salt (X = Li) and subsequent reaction with ketone 9 followed by triethylsilyl protection afforded 6b in 48% yield. Treatment of the same lithium species with iPrOBpin afforded 8bB, which underwent twofold Suzuki-Miyaura coupling with 5, providing 6c in excellent yields.…”
Section: Resultsmentioning
confidence: 99%
“…Third, at the molecular level, effective organic chemical synthesis pathways have been developed for different sp 2 carbons including curved graphene-like carbon with non-hexagon rings. For instance, chemical synthesis routes have been proposed and tested to create nanographene molecules with heptagon, pentagon and even octagon rings [26,208,209], whose equilibrium configurations are warped in 3D space (Fig 21a-c). Another study [153] has demonstrated that designed carbon molecules with both hexagons and non-hexagon rings are capable of folding into curved 3D configurations, like a spherical cap which could serve as a basis to grow carbon nanotubes with controlled chirality.…”
Section: Fabrication Techniques Of Topologically Designed Graphenementioning
confidence: 99%
“…Topological defects have also been shown to alter electronic transport behaviors from high transparency to perfect reflection of charge carriers [19]. Recent experimental advances [24][25][26][27] have made it increasingly possible to control atomic structure and distribution of topological defects, paving the way for large scale fabrication of "topologically designed" graphene structures and devices. [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation